Understanding dietary diversity gains from agronomic-nutritional interventions across age and gender: a longitudinal analysis using repeated measures ANOVA and mixed-effects modeling - Kamal, Mustafa; Md. Arifur Rahaman; Nandi, Ravi; Parupalli, V.L. Bharathi; Aravindakshan, Sreejith; Hossain, Md. Khaled; Krupnik, Timothy J. (TAFSSA, 2024)
This brief presents the results of the Diet Quality Questionnaire (DQQ), examining the influence of age, gender, and agronomic-nutritional interventions across a longitudinal study from January 2023 to February 2024. Data were collected over five discrete time points, capturing dietary patterns and quality across three major agricultural production seasons—Rabi, Kharif I, and Kharif II—in Bangladesh.